Institutionalizing Ethical Reasoning: Integrating the ASA’s Ethical Guidelines for Professional Practice into Course, Program, and Curriculum - Tractenberg, Rochelle E. (Ethical Reasoning in Big Data, 2016)
An emphasis on the application of data mining and other “big data” techniques has raised concerns about ethical use, analysis, and interpretation of large amounts of data obtained from a variety of sources. In 2014, the Committee on Professional Ethics of the American Statistical Association (ASA) initiated a revision of their Ethical Guidelines for Professional Practice, which was completed in 2015. Although interest in these new Guidelines is keen across the ASA membership and leadership, as of the 2013–2014 academic year, only 35 % of universities in the United States required any ethics content for “at least some” of their students in statistics and biostatistics programs. There are two main barriers to increasing this to 100 % of universities and 100 % of students. First is time and effort: either a new (additional) course is needed or time within existing courses must be carved out to accommodate new material. Similarly, teaching and learning about ethics, or professional practice, is qualitatively different— particularly in terms of assessment—than it is around statistics and biostatistics/data analysis. A second barrier is content: it can sometimes seem that “ethics training” is only required for those who violate norms for ethical practice (or the law—by falsifying data, plagiarising, or committing fraud in scientific research). Moreover, most faculty, if they have received training in ethics or in the “responsible conduct of research”, have experienced a major focus on memorization of rules or guidelines and possibly an emphasis on the protection of human subjects and their privacy. However, “statistical practice” involves a great deal more than just the consideration of the human (or animal) subjects in a research study—as does responsible conduct in research. The Guideline principles interact, and sometimes must be prioritized due to their potentially conflicting applicability in any given situation. Therefore, memorization of the Guidelines—or their simple distribution to students or faculty—is unlikely to promote the awareness of their use and importance that is desired by the ASA and the Committee on Professional Ethics that has maintained and revised them. This article outlines elements of the 2015 revision of the ASA Ethical Guidelines for Statistical Practice that are suitable—and important—components of training all undergraduates and graduates whether or not they are statistics majors. It also contains recommendations reflecting current research on how best to promote adult learning—using a constructivist approach consistent with principles of andragogy, and supporting the promotion of the development of expertise, or at least its initiation. Methods for assessment of student work across level (undergrad/grad/post doc/faculty) and context (within major/non-stats majors) are also discussed.